2001
DOI: 10.1097/00007632-200106010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Operative Outcomes of Cervical Compression Myelopathy and MRI of the Spinal Cord

Abstract: The low-signal intensity changes on T1-weighted sequences indicated a poor prognosis. The authors speculate that high-signal intensity changes on T2 weighted images include a broad spectrum of compressive myelomalacic pathologies and reflect a broad spectrum of spinal cord recuperative potentials. Predictors of surgical outcomes are preoperative signal intensity change pattern of the spinal cord on radiologic evaluations, age at the time of surgery, and chronicity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
139
3
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(148 citation statements)
references
References 29 publications
4
139
3
2
Order By: Relevance
“…4 Correlation of SI with spinal cord compression There were researches suggesting that axial sections based on T2-weighted MRI parameters were more reliable in assessing the degree of cervical spinal cord compression than T1-weighted sequences, and TA was reliable and versatile in assessing spinal cord compression. 5 Consistent with consensus that most studies have reported, 8 data from our study support the fact that TA closely correlates with baseline JOA score and surgical outcome. Trying to correlate TA and GSI on MRI, one would expect TA to be larger in patients with lower GSI on MRI.…”
Section: Discusionsupporting
confidence: 91%
See 1 more Smart Citation
“…4 Correlation of SI with spinal cord compression There were researches suggesting that axial sections based on T2-weighted MRI parameters were more reliable in assessing the degree of cervical spinal cord compression than T1-weighted sequences, and TA was reliable and versatile in assessing spinal cord compression. 5 Consistent with consensus that most studies have reported, 8 data from our study support the fact that TA closely correlates with baseline JOA score and surgical outcome. Trying to correlate TA and GSI on MRI, one would expect TA to be larger in patients with lower GSI on MRI.…”
Section: Discusionsupporting
confidence: 91%
“…MRI can show not only the etiology of myelopathy but also the intramedullary state of the spinal cord in detail, 6,7 thereby helping in both the diagnosis and prognosis of CSM. 8,9 To date, postoperative MRI has not yet been fully studied in relation to the correlation of morphology or signal change of cervical cord and longer-term prognosis in CSM patients. In our study, we have focused on quantitative analysis of signal intensity (SI) and transverse area (TA) of the spinal cord on T2-weighted MRI preoperatively and postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…The involved level of the spinal cord was determined using magnetic resonance imaging (MRI) by ascertaining signal intensity changes [18]. If the spinal cord showed signal intensity changes at more than one level, the level showing the most severe compression of the spinal cord was identified as the involved level.…”
Section: Methodsmentioning
confidence: 99%
“…Morio et al 16 reported that low-signal intensity changes on T1-weighted sequences indicated a poor prognosis. They speculated that high-signal intensity changes on T2-weighted images indicated a broad spectrum of compressive myelomalacic pathologies and reflected a broad spectrum of spinal cord recuperative potentials.…”
Section: Discussionmentioning
confidence: 99%